Cr/Pt Ohmic contacts to B₁₂As₂ - Wang, S. H.; Lysczek, E. M.; Liu, Bangzhi; Mohney, S. E.; Xu, Z.; Nagarajan, R.; Edgar, James H. (My University, 2005)
Palladium, Pt, and Cr/Pt contacts to the wide band gap icosahedral boride semiconductor B₁₂As₂ have been studied. All Pd and Pt contacts exhibited nonlinear I-V characteristics, while Cr/Pt contacts were Ohmic. The specific contact resistance was reduced from 6Ω cm² as-deposited to 3x10[superscript]-⁴ Ω cm² after the Cr/Pt contacts were annealed at 750 °C for 30 s in Ar. Annealing at 600 °C or higher drastically reduced the semiconductor sheet resistance, whether annealing was performed before or after metallization. This apparent activation of the semiconductor is a likely cause for the improvement in the Ohmic contacts with annealing.
Keywords: Chemical vapor deposition; Thin films; Growth